Life forms of Orthoptera Belarus as an indicator of their adaptive capabilities and bioindicative qualities - Sergeeva, Tatyana P.; Lozinskaya, Olga V.; Smirnova, Elena G. (Journal of the Belarusian State University. Ecology, 2022)
The literature data on the life forms of Orthoptera are analyzed, and the results of own research are presented. The contribution of the representatives of different scientificschools to the study of the life forms of insects, in particular, Orthoptera, is characterized. It is emphasized that the doctrine on life forms, along with the doctrine on ecological faunal complexes, is an important area in ecology. It is noted that life forms characterize sufficiently precise the features of the living conditions of organisms due to ecological plasticity (including eury- and stenotopy), which is a reflection of their adaptive potential. The affiliation of all Orthoptera species found on the territory of Belarus to a certain life form has been established, their set has been studied. Spectrum has been compiled: it is represented by 16 groups belonging to two classes: phytophiles and geophiles (8 life forms in each). It is noted that most Orthoptera of Belarus belong to the class of phytophiles (34), which includes hortobionts: cereal (real), sedge-cereal, specialized, herbivorous and facultative; as well as tamnobionts, microtamnobiontes and specialized tamnobionts. The class of geophiles (19), but it significantly inferior in the number of constituent species. It includes open and subcover geophiles, herpetobionts, burrowing, groundmoving, eremobiontes, myrmecophiles and active fissurobionts. A rare stenobiont hygrophilous species - Chrysochraon dispar (Germ.) deserves special attention throughout its distribution area. It combines unique features that influence the ecological, phenetic and morphological structure of populations. The data obtained on the Orthoptera properties, which are manifested in the structural organization of their communities and a set of life forms specific to different habitats, allow us to consider this group of insects usable for environmental bioindicator assessment and ecological monitoring.